Efforts to Reduce Carbon Footprint of Dokuz Eylül University Tınaztepe Campus in İzmir, Türkiye - Elif Duyuşen Kokulu; Eylül Ceren Özyürek (Turkish Journal of Agriculture: Food Science and Technology)
Current study intends to find out the carbon footprint of Dokuz Eylül University's Tınaztepe Campus and comprehensively assess its environmental impact in the process. The study provides a detailed analysis of carbon emissions resulting from the campus’s energy consumption, transportation, water usage, and other sources. Based on these analyses, the total CO2 emmission of the campus has been determined, taking into account the carbon sequestration capacity of the university's forested area. Calculations performed using the IPCC Tier 1 Model estimate that Tınaztepe Campus's total annual carbon footprint is 2,458.44 tons of CO2. Additionally, the annual carbon footprint per capita has been calculated as 0.059 tons of carbon footprint. According to the findings, the largest portion of carbon emissions is from natural gas consumption, while the smallest is from water consumption. In light of this data, various strategic recommendations have been developed to reduce the campus’s carbon footprint. These recommendations include measures such as increasing energy efficiency, adopting more sustainable transportation methods, and reducing water consumption. The results of this study provide valuable insights for universities to consider when developing sustainability policies.